MEDICAL EDUCATION AND DILEMMA OF A CLINICAL TEACHER - Masood Ur Rehman (Gandhara University, 2019)
Weas clinicianshave manyjobsto do. Apartfromourfamily, socialandreligious obligations, we teach,treat, manage patients andhave administrative duties. We have beenmeagerlytrained for teaching, administration and other competencies as is evidentfromourundergraduate andpostgraduatemedicalcurriculum. Havingbeengiventherole of a teacher in medical profession, weteach manyundergraduateand postgraduate students, supervise them, regularlytake part in assessments, papercheckingand questions development. The dilemma is; is it not enough for us to be designated asteachers? Ofcourse, bydoing somanythings as mentioned above, we are teachers. Hardenand Crosbyhavedescribed 12roles ofa clinicalteacher1. Clinical teacher isnot just aninformation provider to undergraduate and postgraduatestudents.Rather,aclinicalteacher should be trained enough to developasa role model, mentor, facilitator, learningresourcescreator and provider, course organizerandan evaluator.Teachingat undergraduate andpostgraduate levelneeds conversionfromtiring, longlectures for presenting alotofinformation into objective based,interactive, relevant, and shortlectureskeepingin mindthe learningstyles ofstudents. Thiscan be achieved byfollowingthe Gagne'snineevents ofinstructions2. The clinicalteachersneed to followthese guidelinesto make theirlecturesatpar with internationalstandardsofteaching.Clinicalteachers need tofollowthe new ways ofworkplace-basedteaching andlearning strategieslike one-minute preceptor modelofbedside teachingtoavoid tiring teaching rounds bydiscussingirrelevant topics, without keepinga focus on patient problems3. Theassessment systemneedsa revamp in oureducational system. In addition to goodqualitymultiplechoice questionswe needto convert as wellto keyfeature format and cluster questions to increasestudent's problemsolvingand criticalthinking abilities4. Similarly,short answer questionsneedtobedesigned properlyto increase thereliabilityand validityof assessments. Most ofour ObjectiveStructuredPractical/ClinicalExaminations (OSPE/OSCE)assess the cognitive domain ofstudents but actuallythese areintendedto assess the psychomotor andaffectivedomains. Thisresults in low validityand reliability of our assessments5. Regarding paper checking, a uniform policy for checking should beapplied. This canbe done bydeveloping a proper keyfor each question byusingtheproper principles ofassessment. Role modelling isconsidered to be a powerfultool for learning6. Teacher should developthe attributes ofa good rolemodelto have an impact over student's learning. Thesystemoffeedback israre inourundergraduate and postgraduate medical institutions. Feedbackisconsideredtobethebackbone ofa teaching organisation7, and we the teachersneedto learn, applyand habituate feedbackin our culture. Evaluationstrategies for our teaching, patient's management, administrative actions needto beappliedand necessarycorrectionsto bedone. Toovercome all theseshortcomingson part of clinicalteachers, itismandatoryfor teachersto enroll in amedical education program. These programsare in the form of certificates (6 months), diploma andmaster degree programs (2 years),and doctoralprograms. In thecomingyears, the Pakistan Medicaland DentalCouncil(PM&DC)isconsideringthese programsmandatoryfor promotion offacultyfromassociate professor to the post ofprofessor andappointment ofprincipals and deansof educationalinstitutions. These programs revolve around sixbasic concepts ofmedicaleducation;educational psychology, teachingand learning,curriculum,assessment, research, professionalismand academicleadership.Ifwe lagbehind in the concept of"Train theTrainee", wewillremain in a dilemma and continueto march to the beat ofourown drumthinking thateveryoneelse isoutof step. The clinicalteacherscan improve these skillsbyenrollingthemselves in these educational programsoftheir choice to bring theteaching, assessments, research,and professionalism at par with international standards.